Biochemical assessment of histochemical methods for oestrogen receptor localisation. Issue 4 (April 1982) - Underwood, J C; Sher, E; Reed, M; Eisman, J A; Martin, T J
Abstract : The biochemical validity of published labelled-ligand and ligand-antibody methods for the histological localisation of oestrogen receptors (ER) in breast carcinomas was assessed by measuring specific and non-specific binding of 3H-oestradiol to pretreated MCF-7 monolayers; the monolayers had been either frozen and thawed, then air-dried or acetone-fixed, or fixed in formaldehyde to reproduce the conditions in published methods. The results indicate that most of the ER in a frozen section is likely to be lost by diffusion into the supernatant incubation medium. Fixation substantially restricts diffusion but reduces specific oestradiol binding and may increase non-specific binding; acetone fixation is particularly deleterious. Preincubation in oestradiol fails to protect the receptor during fixation. We conclude that the published histochemical methods for ER localisation have doubtful validity and should not yet be used in preference to conventional biochemical assays.